Students' Visual-Spatial Thinking Ability in Solving Geometry Transformation Problems Based on Jombangan Ethnomathematics in Junior High Schools - Masamah, Ulfa; Farabi, Muhammad Al (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED), 2024)
Students must have visual-spatial thinking ability in order to understand geometric transformation material which is abstract in nature and requires imagination. This research aims to analyze students' visual-spatial thinking abilities in solving geometric transformation problems based on Jombangan ethnomathematics in junior high schools. This research uses a qualitative approach with a descriptive type. The subjects of this research were class VIII students at MTs Negeri 3 Jombang who were determined using purposive sampling. Data collection techniques were carried out using tests in the context of Jombangan ethnomathematics, semi-structured interviews, observation, and documentation. The data analysis technique uses three steps, namely data reduction, data display, and conclusion/verification. The credibility test is carried out by triangulating methods and increasing persistence. The results of this research show that students at MTs Negeri 3 Jombang achieve the indicators of pattern searching and imagining more dominantly, while the indicators of problem solving and conceptualization are still lacking.